A new experimental technique for positive ion drift velocity measurements in noble gases: Results for xenon ions in xenon - Neves, P. N. B. (2007)
A new technique is described for measuring the drift velocities and mobilities of noble gas ions in noble gases that makes use of a gaseous electron multiplier (GEM) and a UV flash lamp to produce the ions in a thin, well-defined, planar region. The drift velocities are determined from measurements of the transit time of the ions in crossing the drift space. We present experimental results for xenon ions in xenon. For these ions, the reduced mobility values measured at various pressures when E/N-->0 fall within the interval [0.70, 0.74] cm2 V-1 s-1. A discussion of the results concerning the existence of Xe+, , , etc., ions is also made.